2018
DOI: 10.1111/add.14252
|View full text |Cite
|
Sign up to set email alerts
|

Testing associations between cannabis use and subcortical volumes in two large population‐based samples

Abstract: In exploratory analyses based on young adult and middle-aged samples, normal variation in cannabis use is unrelated statistically to individual differences in brain morphology as measured by subcortical volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 78 publications
(131 reference statements)
1
19
3
Order By: Relevance
“…The present results differ from those of Gillespie et al 31 and Chye et al 20 , in which results indicated an absence of association between non-clinical levels of cannabis use and hippocampal or amygdalar morphometry. One likely reason for this is the improved resolution of the measurement of cannabis use in the current study, which measured cannabis use using both selfreported and biological measures, assessed for use both past and recent used, and distinguished between problematic and non-problematic cannabis use.…”
Section: Cannabis Hippocampus Amygdala: 15contrasting
confidence: 99%
See 1 more Smart Citation
“…The present results differ from those of Gillespie et al 31 and Chye et al 20 , in which results indicated an absence of association between non-clinical levels of cannabis use and hippocampal or amygdalar morphometry. One likely reason for this is the improved resolution of the measurement of cannabis use in the current study, which measured cannabis use using both selfreported and biological measures, assessed for use both past and recent used, and distinguished between problematic and non-problematic cannabis use.…”
Section: Cannabis Hippocampus Amygdala: 15contrasting
confidence: 99%
“…One exception includes a study by Chye et al that examined 22 non-dependent cannabis users, finding them not to differ from healthy controls in hippocampal volume 20 . Additionally, the largest investigation of cannabis use in a non-clinical sample to date was a two-part study, with study one including 622 young adults and study two including 474 middle-aged men drawn from the general population; this investigation also did not find associations between hippocampal or amygdalar volume and cannabis use in either study after correcting for multiple comparisons 31 .…”
Section: Cannabis Hippocampus Amygdala:mentioning
confidence: 97%
“…Preclinical evidence has consistently demonstrated a causal relationship between cannabis exposure and changes to brain morphology (for review, see Panlilio and Justinova, 2018). The human evidence, however, has been variable reporting both increases and decreases in brain volumes (Ashtari et al, 2011;Cousijn et al, 2012;Gilman et al, 2014), no volume differences (Jager et al, 2007;Weiland et al, 2015;Gillespie et al, 2018), and modest effect sizes (Weiland et al, 2015). Factors including the age of cannabis use initiation, comorbid substance use, and levels of use are believed to contribute to variability in the human findings (Curran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dose-dependent associations with brain volumes have been reliably identified in preclinical studies (for review, see Lorenzetti et al, 2010) with some evidence of the same in humans (Battistella et al, 2014;French et al, 2015), suggesting consequences of lower levels of use. One study has reported differences in gray-matter density and shape of the amygdala and nucleus accumbens in recreational cannabis users (Gilman et al, 2014), but subsequent research has suggested that these findings may be associated with alcohol (Weiland et al, 2015) and nicotine (Gillespie et al, 2018) exposure in the cannabis users.…”
Section: Introductionmentioning
confidence: 99%
“…In the UKB, smoking status was associated with thickness and surface of the thalamus (left and right), although we also found associations with the caudate and pallidum. Previous studies have reported association between tobacco usage and volume of left thalamus (Gallinat et al, 2006; Gillespie et al, 2018; Hanlon et al, 2016), which might be due to faster age related volume loss in smokers (Durazzo et al, 2017). We did not replicate other cortical or subcortical associations previously reported (Gallinat et al, 2006; Hanlon et al, 2016; Prom-Wormley et al, 2015).…”
Section: Discussionmentioning
confidence: 94%